2021
DOI: 10.2967/jnumed.120.252791
|View full text |Cite
|
Sign up to set email alerts
|

Anti-CEA Pretargeted Immuno-PET Shows Higher Sensitivity Than DOPA PET/CT in Detecting Relapsing Metastatic Medullary Thyroid Carcinoma: Post Hoc Analysis of the iPET-MTC Study

Abstract: Introduction. Pretargeting parameters for use the anti-CEA (carcinoembryonic antigen) bispecific monoclonal antibody TF2 and the 68 Ga-labeled IMP288 peptide ( 68 Ga-IMP288) for Immuno-PET have been optimized in a first-in-human study performed in MTC (medullary thyroid carcinoma (MTC) patients (iPET-MTC study). The aim of this post-hoc analysis was to determine the sensitivity of Immuno-PET in relapsing MTC patients, in comparison with conventional imaging and 18 F-DOPA PET/CT (DOPA-PET/CT). Methods. Twenty-f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 33 publications
(53 reference statements)
0
14
0
1
Order By: Relevance
“…After the comprehensive computerized search was performed and references lists were extensively crosschecked, our research yielded 1618 records on or before April 11, 2022, including 411 articles from Pubmed, 739 articles from Web of Science, 460 articles in Embase, 8 articles from Cochrane Library, 5 articles from references. Excluding the duplicates, unrelated topics, unoriginal clinical studies, non-English articles, and studies without original data, 19 full-text articles [3,12,17,19,[31][32][33][34][35][36][37][38][39][40][41][42][43][44] were assessed for possibly eligible. Finally, 9 studies [3,19,[32][33][34]37,39,41,44] were selected because of the eligibility for the systematic review and network meta-analysis.…”
Section: Literature Search and Selection Of Studiesmentioning
confidence: 99%
“…After the comprehensive computerized search was performed and references lists were extensively crosschecked, our research yielded 1618 records on or before April 11, 2022, including 411 articles from Pubmed, 739 articles from Web of Science, 460 articles in Embase, 8 articles from Cochrane Library, 5 articles from references. Excluding the duplicates, unrelated topics, unoriginal clinical studies, non-English articles, and studies without original data, 19 full-text articles [3,12,17,19,[31][32][33][34][35][36][37][38][39][40][41][42][43][44] were assessed for possibly eligible. Finally, 9 studies [3,19,[32][33][34]37,39,41,44] were selected because of the eligibility for the systematic review and network meta-analysis.…”
Section: Literature Search and Selection Of Studiesmentioning
confidence: 99%
“…The first clinical trial of pretargeted PET with TF2, a bispecific trivalent mAb of anti-CEA × anti-HSG, in relapsing MTC patients showed high tumor uptake ( 285 ). Moreover, the TF2 probe had superior sensitivity over [ 18 F]fluoro-l-dopa ([ 18 F]FDOPA) PET/CT ( 148 , 286 ) and CT ( 286 ) in detecting metastatic lesions.…”
Section: Immunopet In Different Malignanciesmentioning
confidence: 99%
“…In the last 2 y, additional clinical studies with TF2/ 68 Ga-IMP288 were performed on CRC (113) and HER2-negative/CEA-positive metastatic breast cancer patients (114). In 2021, Bodet-Milin et al reported clinical data using TF2/ 68 Ga-IMP288 in MTC patients, demonstrating improved sensitivity for metastatic lesion detection over 18 F-L-dihydroxyphenylalanine PET/CT (115). Select examples of recent clinical PRID studies with TF2/IMP288 are shown in Figure 4.…”
Section: Bsab Pretargetingmentioning
confidence: 99%